Structural Change in Production and Trade: A Panel Data Analysis (Journal of Asian Development Studies, 2020)
Trade and foreign direct investments (FDI) in theory, have a positive impact on spillover of technology, demand for human capital and skilled worker wages, profits and total factor productivity. Rising competition conditions in world level cause and/or empower to the change in either production structure or factor endowments. Beside fast improving in information technologies, FDI and trade relations conveying the major role on this process.  Free trade conditions and better investment climates contribute to improvements in skilled labor supply and its impact on economic fundamentals by affecting the product variety and quality through structural changes in factor endowments. Especially the rise in skilled labor capacities of developing world contributing more to change the landscape of the factor endowments. Within this context, production activities resulting with new production models in which the production stages segmentation through more than one country. As a result, comparative advantages of advanced economies in high tech sectors should be easing in time against emerging countries. In this study, we research these developments via panel data regressions and cross table analysis  in which FDI and both total and high-tech goods’ trade developments examining in countries/regions China, US, Japan and EU in 2001-2009 period.